A River in the City of Fountains : An Environmental History of Kansas City and the Missouri River - MALLEA, AMAHIA (Book collections on Project MUSE., 2018)
"In A River in the City of Fountains, Amahia Mallea brings the Missouri River to the forefront of Kansas City's history and shows how deeply the two are entwined. The river has always been ubiquitous, its waters found in pipes, toilets, fountains, breweries, and fire hoses--and yet, unlike many other cities, KC is not a place where the river factors into public life. Mallea centers her argument on the idea of health--of people, of communities, of the river. She describes the commitment regional planners and economic interests had to managing the river for barge traffic long after the decline of river transport and the rise of railroads and highways. Water issues from floods to pollution impacted the city unevenly, and for many decades the river neighborhoods were considered undesirable, with the wealthiest Kansas Citians moving to higher ground. Local public health officials struggled to gain the support and action of competing municipal and state governments and interests, and not until federal efforts like the Clean Water Act and the Environmental Protection Agency came into being did public health become a significant consideration in KC river management. Ultimately, Mallea argues that the river has always connected people and placed them in wider environmental and social relationships--particularly through public health. But if that connection is hidden away from the life of the city, than how can residents see its importance? Slowly, with public support and federal legislation, Kansas City is in the midst of reviving its relationship with its rivers--and broadening its idea of who and what makes a healthy river and a healthy city"--